Perbandingan Arachis pintoi dengan Tanaman Kacang-kacangan Penutup Tanah Lain dalam Menekan Laju Erosi pada Lahan Kelapa Sawit Berbukit - Sarjono, Arif; Guntoro, Dwi; Supijatno, dan (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2019)
Land preparation of oil palm plantation in hilly areas is vulnerable to environmental degradation. Legume cover crops can be used in vegetation system for soil conservation to control erotion. Arachis pintoi is a legume potential for cover crop. The objective of the research was to study the role of A. pintoi in suppressing soil erosion rate in oil palm land with the topography of hilly land. The research was conducted on the land of Bukit Kemuning farmer group, Mersam, Batanghari, Jambi with an average slope of 22.8% from September 2017 to March 2018. The experimental design used was a single-factor randomized complete block design with five treatments and four replications. The treatment consisted of natural vegetation, Arachis pintoi, Centrosema pubescens, Pueraria javanica and Calopogonium mucunoides. The results showed that the rate of increased leaf number of A. pintoi was 13.6 pieces per week and could cover the ground surface 100% at 20 weeks after planting (WAP). The dry weight of A. pintoi biomass was 496.08 g m-2 at 20 WAP. A. pintoi suppressed soil erosion by 80.45% as compared to natural vegetation treatment. However, it was not significantly different on suppression rates to other biomulch treatments.Keywords: biomass, Calopogonium mucunoides, Centrosema pubescens, land cover crop, Pueraria javanica